Quality Assurance: Managing Education for School Improvement - Mba, Callistus Okechukwu; Ugwulashi, Chima Sebastine (Advances in Social Sciences Research Journal, 2019)
Quality assurance has different definitions by different authors. The issue of quality assurance has become the central theme for higher education in many countries of the world and Nigeria is no exception. This is because it is an all embracing effort covering all policies and actions. Hindrances of quality assurance and strategies for improvement of quality assurance were all discussed. Theories of quality assurance management, quality assurance management practices, improvement to quality assurance were also torched. Quality teaching as a sine-qua-non to quality assurance, factors for improving quality assurance in schools was looked into. Conclusion was made in while suggestions were outlined which one of them is (1) government should as a matter of necessity vote more funds for the sustenance of quality assurance in our institutions.